Effective Questioning Techniques - James E. Dyer (EDIS)
WC084, a 6-page fact sheet by James E. Dyer, discusses the purpose of questioning in the classroom, types of questions, how to maximize student participation, providing sufficient wait time, handling student responses, and responding to student questions. Includes references and Blooms Taxonomy Reference Guide. Published by the UF Department of Agricultural Education and Communication, December 2008.